2013
DOI: 10.1097/iop.0b013e31827defe1
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Midfacial Seal Drape in Reducing Oculofacial Surgical Field Fire Risk

Abstract: A midfacial seal drape reduced oxygen concentrations from nasal cannula oxygen in the oculofacial surgical field and may reduce fire risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…2,3 A similar midface draping technique described by Tao et al has been shown to mitigate this risk by limiting the flow of supplemental oxygen toward the surgical field. 4 The adhesive 1010 drape should be well sealed across the face to minimize any potential gaps that can serve as tunnels for passage of oxygen or aerosols. 5,6 Our draping technique differs from the method described by Tao et al in that the entire inferior portion of the drape is elevated, rather than using a small venting slit at the chin.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A similar midface draping technique described by Tao et al has been shown to mitigate this risk by limiting the flow of supplemental oxygen toward the surgical field. 4 The adhesive 1010 drape should be well sealed across the face to minimize any potential gaps that can serve as tunnels for passage of oxygen or aerosols. 5,6 Our draping technique differs from the method described by Tao et al in that the entire inferior portion of the drape is elevated, rather than using a small venting slit at the chin.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of other posited solutions include a midfacial seal drape, discontinuation of nasal cannula, supplemental oxygen delivery via a modified nasopharyngeal tube further sealed with an ipsilateral ear plug in the nares, supplying sub-100% oxygen-gas mixtures via nasal cannula, air delivery at 5 to 10 LPM under the drapes to dilute the OEA, and cessation of supplemental oxygen for MAC cases altogether. 36-41…”
Section: Discussionmentioning
confidence: 99%
“…Minimization of oxygen delivery at all times and avoidance of (1) drape tenting and (2) creation of an OEA beneath the drapes that easily connects to the surgical field are broadly accepted recommendations. Examples of other posited solutions include a midfacial seal drape, discontinuation of nasal cannula, supplemental oxygen delivery via a modified nasopharyngeal tube further sealed with an ipsilateral ear plug in the nares, supplying sub‐100% oxygen‐gas mixtures via nasal cannula, air delivery at 5 to 10 LPM under the drapes to dilute the OEA, and cessation of supplemental oxygen for MAC cases altogether 36‐41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…j Suctioning/scavenger systems completely inhibit and/or reduce the qualitative severity of surgical fires [12,13]. j A mid-facial seal drape may reduce the intraoperative ORE [14].…”
Section: Role Of the Oxidizermentioning
confidence: 99%